Evaluation of Noncommercial Ultrasound Gels for Use in Resource‐Limited Settings. (24th July 2018) - Vinograd, Alexandra M.; Fasina, Abiola; Dean, Anthony J.; Shofer, Frances; Panebianco, Nova L.; Lewiss, Resa E.; Gupta, Saurabh; Rao, A. K. Raja; Henwood, Patricia C.
Abstract : Objectives: Ultrasound (US) is increasingly used in settings where commercial US gel is unavailable. This study evaluated noncommercial gel recipes compared to commercial gel. Methods: A search for US gel formulations revealed 6 recipes. Half‐strength commercial gel and a modified glucomannan recipe were also tested. Nine gels, including commercial gel, were tested in Liberia and the United States. In each session, 2 physician sonologists evaluated 9 gels on 2 models, obtaining videos from the hepatorenal space with a curvilinear transducer, the cardiac parasternal long view with a phased array transducer, and the left basilic vein with a linear transducer. The sonologists and models, who were blinded to gel identity, made independent quantitative and qualitative gel evaluations comparing the test gel to commercial gel. Two physician sonologists who were blinded to the gel identities and a US operator reviewed the images and rated their quality. An analysis of variance in repeated measures was performed to test for differences in the overall score, real‐time quality, and other characteristics. Post hoc pairwise comparisons to commercial gel were performed with a Tukey‐Kramer adjustment. Inter‐ and intra‐rater reliability was calculated for the image review. Results: Commercial gel earned a perfect score. Compared to commercial gel, xanthine gum gel scored highest, followed by half‐strength commercial gel. Hot concentrated glucomannan and cold glucomannan gel were found to be significantly worse than commercial gel. No significant difference was found between images based on the gel used on the image review. Conclusions: No significant difference in image quality was found between commercial and noncommercial gels on US image review.